2015
DOI: 10.3109/09638237.2015.1022251
|View full text |Cite
|
Sign up to set email alerts
|

The post-stroke depression and its impact on functioning in young and adult stroke patients of a rehabilitation unit

Abstract: More than half of the PSD patients had a moderate degree of depression. Significant correlations were noticed between depressive symptoms and functional status evaluated both by an instrument of assessing stroke impact upon general health and an instrument for assessing the everyday activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…Identification of patients with stroke who have depression can be difficult when there are language and cognitive impairments [ 28 ]. Those with post-stroke depression might be less likely to participate in rehabilitation therapies, be less compliant with medications, feel more fatigue, have less appetite, and generally have poorer post-stroke outcomes [ 29 30 ]. Post-stroke depression can also contribute to post-stroke mortality [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of patients with stroke who have depression can be difficult when there are language and cognitive impairments [ 28 ]. Those with post-stroke depression might be less likely to participate in rehabilitation therapies, be less compliant with medications, feel more fatigue, have less appetite, and generally have poorer post-stroke outcomes [ 29 30 ]. Post-stroke depression can also contribute to post-stroke mortality [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the beneficial effects of physical activity on balance in elderly [31,32], after ankle instabilities or fractures [1] or on the quality of life in people with chronic diseases [33,34]. The effects of physical exercises on postural balance have been investigated by Jakobsen et al They found an improvement in postural control after 12 weeks of training [35].…”
Section: Discussionmentioning
confidence: 99%
“…The precision of the IADL scale is sensible even when patients experience MCI, while the accuracy of the ADL scale is higher when patients experience more severe cognitive impairment and dementia [24,25]. Depression is associated with a substantial reduction in quality of life [26]. Depression can be seen more often with ageing.…”
Section: Atrial Ivs -Interventricular Septum Lvpw -Left Ventricularmentioning
confidence: 99%